Using wood-shred, rice-straw and brush-wood-dams with planting seedlings to runoff and erosion control in a forest road fill slope - Fakhari, Mohammad Ali (Array, 2019)
This study aimed to investigate the effects of two types of natural geotextiles, including wood shred (WS), rice straw (RS) and the biomechanics method of brush wood dam (BWD) with planting seedlings of Alnus glutinosa and Salix alba on runoff, soil loss and fill slope. The effects were compared with those obtained from control treatment. A total of 36 plots (2×4m) with three replicates in the direction of gradient to fill slope of a forest road in northern Iran was considered. Soil moisture, canopy cover of seedlings, vegetation coverage, runoff, sedimentation and erosion were measured in plots during 12 months. BWD and WS played an effective role in reducing runoff by 57% and 73%, respectively. By using RS and WS, the sediment concentration was decreased by 23% and 11%, respectively, while by using BWD it increased by 58%. RS (24.16%) and BWD (7%) had the greatest and smallest impact on reducing vegetation coverage, respectively. BWD (33%) and RS (27%) had the highest and lowest canopy cover of seedlings, respectively. Results showed that both RS (22.23%) and A. glutinosa (4.96%) had the greatest effects on increasing soil moisture. Comparison between the planted species and the control treatment (with no seedlings) showed that S. alba was effective in reducing runoff (46.22%), while A. glutinosa was effective in reducing erosion (66.89%) and sediment concentration (53.52%). Finally, interactions between conservation treatment and planting of seedlings played a more effective role in controlling runoff and erosion. Therefore, the application of conservation treatments together with planting of seedlings is recommended in order to provide better soil conservation and restoration of fill slope.